Analisa Tekuk Kolom Baja Ringan (Zincalume) Dan Baja Konvensional - Husni Thamrin; Ferry Anderson S. (Universitas Medan Area, 2023)
Steel column structures can be used for various types of buildings, various advantages can be obtained when using steel as a building material, but its use cannot be estimated. Each of these elements will bear forces such as moments, normal or latitude, although the percentages differ from one another. Structures that carry normal forces are generally found in columns, both compressive and tensile so that a normal stress occurs. At this time the framework for the column is conventional steel but at this time there are other alternative materials, namely frames made of mild steel. As we know so far that most of the use of mild steel for roof truss construction, technological advances in the field of steel materials, especially mild steel, have been able to produce high quality mild steel, namely with a minimum tensile strength of 550 MPa. (Zincalume). Based on the results of the analysis, there is a critical stress difference in two cross sections with the same size from different types of materials, namely mild steel and conventional steel.